1995
DOI: 10.1159/000127058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tetrodotoxin on Osmotically Stimulated Central and Peripheral Vasopressin and Oxytocin Release

Abstract: Tetrodotoxin (TTX) was used to (1) distinguish between axonal and dendritic/ somatic release of vasopressin (VP) and oxytocin (OT) within the supraoptic nucleus (SON) and (2) to determine whether neuronal inputs trigger intranuclear peptide release in the response to osmotic stimulation. Microdialysis was used to administer TTX (10-6 M or 10–4M) bilaterally into the SON with simultaneous monitoring of central and peripheral peptide release and mean arterial pressure in urethane-anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…2, in Shahar et al, 2004). In this regard, it is interesting to note that osmotically stimulated OXT and AVP release is also blocked by application of TTX to the HNS (Ludwig et al, 1995) and that the expected increased in Avp hnRNA under these conditions is also inhibited (see Fig. 1D in this paper).…”
Section: Discussionmentioning
confidence: 51%
“…2, in Shahar et al, 2004). In this regard, it is interesting to note that osmotically stimulated OXT and AVP release is also blocked by application of TTX to the HNS (Ludwig et al, 1995) and that the expected increased in Avp hnRNA under these conditions is also inhibited (see Fig. 1D in this paper).…”
Section: Discussionmentioning
confidence: 51%
“…2) Although experimental evidence from in vitro or electronmicroscopic studies is missing, OXT may directly act at the dendritic level to locally inhibit exocytotic processes related to AVP release. A dissociation of dendritic release and the electrical activity of neuropeptidergic neurons has been established (11,36). 3) Alternatively, OXT could modulate excitatory or inhibitory inputs to AVP neurons identified preor postsynaptically within the SON (7,8; for a review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrates the ability of neuronal cells to independently regulate neuropeptide release from various neuronal elements (axon terminals vs. dendrites and somata). With respect to dendritic release, it has been revealed that intrahypothalamic neuropeptide release can occur independently of the electrical activity (11,36), which is required for axonal neuropeptide secretion. Furthermore, locally released neurotransmitters/neuromodulators, including AVP itself (21,63), GABA (17,28,29) and taurine (15,26,52) were recently considered to regulate basal and stimulated activity of neurohypophyseal AVP (and also OXT) neurons and, thus, AVP secretion into blood.…”
mentioning
confidence: 99%
“…The reverse treatment, chronic hypernatremia, did not alter the survival of the axotomized MCNs in one study (Dohanics et al, 1996); however, in another study that used a chronic intermittent saltloading paradigm, there was an increase in the survival of MCN cells (Huang and Dellmann, 1996). In view of these reports, we tested the hypothesis that after axotomy, neural activity was neuroprotective in the HNS by directly inhibiting both electrical and synaptic activity unilaterally in the SON by local superfusion of TTX (Ludwig et al, 1995) in vivo. Each animal's contralateral SON served as the (noninhibited) control in these experiments.…”
Section: Discussionmentioning
confidence: 99%